Successful criteria for placemaking process in contested spaces: evaluation of non-governmental organisations at Ledra Street Crossing Point in Nicosia - Orac, Ediz; Dagli, Ugur Ulas (Palgrave Macmillan Ltd, 2024)
As adivided capital city, Nicosia and its Buffer Zone have attracted attention across political, social, cultural, and academic spheres since the 1974 division of Cyprus. The Buffer Zone's physical and symbolic presence reflects the ongoing struggle for reunification and the challenges of tension in a confined space. The crossing points in the Buffer Zone serve as bridges, facilitating movement and interaction between the communities. Thus, contested spaces require comprehensive, context-sensitive approaches that foster inclusive dialogues, and seek innovative spatial arrangements to promote sustainable peace and shared understanding. The paper proposes a placemaking process approach that serves as a transformative tool to tackle the difficulties associated with contested spaces and strive towards their comprehensive revitalisation. 126 different NGOs participated as stakeholders in the Ledra Street Crossing Point and answered the Likert scale survey after the reliability check. The aim of this paper is to identify a successful placemaking process diagram for contested spaces as an analytical framework. The diagram establishes important criteria and their correlations for the placemaking process. It identifies sociability alongside uses and activities as key imperatives for successful placemaking process in contested contexts: social networks, sharing space use, multifunctionality, and public space usage.
Keywords: Contested spaces; Placemaking process; Non-governmental organisations; Buffer zone; Nicosia